Technological Innovation and Initial Public Offerings - Maksimovic, Vojislav; Pichler, Pegaret (Review of Financial Studies, 2001)
This article shows how both technological and competitive risks affect the timing of private and initial public offerings in an emerging industry. Early private financing occurs in industries that are perceived to be risky, with high development costs and low probability of being displaced by technologically superior rivals. Early public financing occurs in industries perceived to be viable, with low development costs and low probability of displacement. Due to feedback effects between financial and product markets, the value of investors’ proprietary information is greater in private than in initial public offerings. This has implications for underpricing.